2022
DOI: 10.1029/2022ja030573
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Poynting Flux Statistics From the Swarm Mission: How Much Is Being Underestimated at Larger Scales?

Abstract: The energy transfer rate between the magnetosphere and the ionosphere-thermosphere via field-aligned currents, known as the Poynting flux, quantifies the impact of space weather changes on the atmosphere of Earth. The magnetosphere-ionosphere-thermosphere (MIT) system at high-latitudes is strongly coupled, resulting in Poynting flux transfer significantly affecting many atmospheric features (such as field-aligned currents and neutral density perturbations). In addition to the energy flux from precipitating par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…They also showed that, consistent with previous reports by Pakhotin et al (2021) for Alfvénic PF, there is a clear preference for excess northern hemisphere deposition of PF. Billett et al (2022) and Cosgrove et al (2022) recently confirmed the northern hemispheric PF preference in re-processed Fast Auroral Snapshot data and Swarm data, respectively. The present paper provides more detail about the processing and inter-comparison of spacecraft data that support the multiyear analysis in Knipp et al (2021) and will support future research.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…They also showed that, consistent with previous reports by Pakhotin et al (2021) for Alfvénic PF, there is a clear preference for excess northern hemisphere deposition of PF. Billett et al (2022) and Cosgrove et al (2022) recently confirmed the northern hemispheric PF preference in re-processed Fast Auroral Snapshot data and Swarm data, respectively. The present paper provides more detail about the processing and inter-comparison of spacecraft data that support the multiyear analysis in Knipp et al (2021) and will support future research.…”
mentioning
confidence: 68%
“…Billett et al. (2022) and Cosgrove et al. (2022) recently confirmed the northern hemispheric PF preference in re‐processed Fast Auroral Snapshot data and Swarm data, respectively.…”
Section: Introductionmentioning
confidence: 85%
“…In turn, understanding the plasma composition and its dynamics allows to construct more accurate maps of species density profiles, estimate characteristic timescales for significant events, and potentially infer more accurately the degree of electromagnetic coupling between the subsystems. Besides the so-called transition height (i.e., the altitude where [O+] = [H+]), the balance of light and heavy (primarily O+) ions determines the Alfven speed which is an important parameter in MIT coupling through its relationship with integrated Pedersen conductance to form the reflection coefficient governing downwards Poynting flux (Lysak 1991;Knudsen et al 1992;Pakhotin et al 2018Pakhotin et al , 2020Pakhotin et al , 2021Billett et al 2022). In addition, the propagation of magnetospheric plasma waves such as electromagnetic ion cyclotron (EMIC) waves, which play a significant role in radiation belt dynamics (e.g., Shprits et al 2008), is governed by the relative abundances of ion species.…”
Section: Introductionmentioning
confidence: 99%
“…[O+]=[H+]), the balance of light (primarily H+) and heavy (primarily O+) ions determines the Alfven speed which is an important parameter in MIT coupling through its relationship with integrated Pedersen conductance to form the re ection coe cient governing downwards Poynting ux (Lysak, 1991, Knudsen et al, 1992, Pakhotin et al, 2018, 2021, Billett et al, 2022. In addition, the propagation of magnetospheric plasma waves such as electromagnetic ion cyclotron (EMIC) waves, which play a signi cant role in radiation belt dynamics (e.g.…”
Section: Introductionmentioning
confidence: 99%